Creation of models for forecasting banks' net incomes from currency operations - M F Gumerov (RUDN Journal of Economics, 2012)
In the present article the author has the aims, such as identifying the role of net incomes from currency operations in the process of forming commercial banks' profit, exploring present models for forecasting their size and creation new ones, which take in account different factors which influence on it. They're created on the base of system structural, correlation and factorial analysis. In the result of this investigation the new models were received, they express the specific of each kind of currency operations (conversion, loans and deposits and cash settlement), and the model for the common net income from all kinds of currency operations.